Immunological correlates of cure in the first American Cutaneous Leishmaniasis patient treated by immunotherapy in Argentina. A case report - García Bustos, María Fernanda; Barrio, Alejandra Beatriz; Parodi Ramoneda, Cecilia María; Ramos, Federico; Mora, María Celia; Convit, Jacinto; Basombrío, Miguel Angel (Investigación Clínica, 2012)
A patient with localized cutaneous leishmaniasis due to Leishmania (Leishmania) amazonensis infection was treated with an antigen containing heat-killed L. (L.) amazonensis promastigotes plus BCG. Expression of T-cell differentiation, memory and senescence receptors markers were analyzed on T cell subpopulations, in order to establish the correlation between the percentages of expression of these receptors and his clinical status, at different stages of his follow up. The following case reports on the achievement of a successful clinical outcome with complete resolution after receiving immunotherapy. A thorough clinical and immunological follow up supporting the healing process of this patient”™s lesion is presented in detail.